Contatti tra le lingue e culture nell'Adriatico Orientale - Deželjin, Vesna (2008)
The article discusses examples of linguistic and cultural contacts on tne Eastern Adriatic, namely from Trieste to Dubrovnik, which are documented by the presence of German, Croatian, Slovenian and Latin loan words in the koinè ; ; of Italian type, used either in literary texts or spoken by local people
Projekt MZOS
ITA